RISK STUDY OF SUPPLY CHAIN OF LEARNING MODULE PROCUREMENT PROJECT (CASE STUDY: PT. XYZ) - Rheza Aulia Ramadhan; Ananda Vania Arisa Putri; Bambang Purwanggono Sukarsono (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Modern era has an impact on the industry. Relate to technology to turn raw goods into finished goods. Look at competitive in competition between companies that are required to customer demand. PT. XYZ is a publishing and printing company, constructing and concocting books and learning modules. Currently PT. XYZ does not yet have structured risk management to identify and mitigate risks that occur primarily in supply chain functions. Therefore, research is needed that aims to identify possible risks in PT. XYZ supply chain activities. Determine the cause of risk that must be prioritized to be mitigated in the supply chain PT. XYZ and determine mitigation strategies that must be prioritized to address the causes of risks in the supply chain PT. XYZ. The method used in this study is by the House of Risk method. HOR is used to identify risk events, risk agents in the supply chain and design mitigation strategies for risk agents based on ARP (Aggregate Risk Potential) value. The results of this study show that there are 10 risk events and 15 risk agents that become supply chain risks as well as recommendations for tackling priority risk agents.